Mathematical Methods in Modern Scientific Knowledge and Mathematical Style of Thinking (Texas Journal of Multidisciplinary Studies, 2023)
Mathematical methods in the modern theory of knowledge are considered, the possibilities of applying mathematics in various fields of science are shown.